Peningkatan Pemahaman Konsep Matematis Melalui Blended Learning Berbantuan Quizizz Ditinjau dari Disposisi Matematis Siswa - Albab, Novita Ullil; Hakim, Lukman El; Aziz, Tian Abdul (Jayapangus Press, 2025)
The low level of students' conceptual understanding in mathematics, along with the lack of technological integration in learning, remains a major challenge in mathematics education in Indonesia. This study aims to evaluate the effectiveness of the Blended Learning model assisted by the Quizizz application on students’ conceptual understanding in mathematics, considering students’ mathematical disposition as a moderating factor. The study employed a quasi-experimental method with a posttest-only control group design and a 2×2 treatment by level approach. The participants consisted of four eighth-grade classes selected through cluster random sampling at a public junior high school in Jakarta. The research instruments included a mathematical disposition questionnaire and a conceptual understanding test, both validated by experts. Data were analyzed using independent sample t-tests and the General Linear Model (GLM) Univariate, based on the statistical assumptions of each research objective. The results indicated that the Blended Learning model assisted by Quizizz effectively improved students’ conceptual understanding, particularly among those with low mathematical disposition. However, no significant difference was found among students with high disposition, nor was there a statistically significant interaction between the learning model and mathematical disposition. These findings suggest that although the effectiveness of Blended Learning is not significantly dependent on students’ disposition, it remains a promising instructional approach that is inclusive, adaptive, and responsive to the diverse needs of learners in the digital era.